2009
DOI: 10.1111/j.1399-0004.2009.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations in three children with sudden infant death

Abstract: Sudden death of an infant is a devastating event that needs an explanation. When an explanation cannot be found, the case is labeled as sudden infant death syndrome or unclassified sudden infant death. The influence of genetic factors has been recognized for sudden infant death, but copy number variations (CNVs) as potential risk factors have not been evaluated yet. Twenty-seven families were enrolled in this study. The tissue specimens from deceased children were obtained and array-based comparative genomic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 16 publications
(26 reference statements)
1
32
0
1
Order By: Relevance
“…CNVs that effect critical developmental genes may cause disease. Toruner et al investigated 27 SIDS cases, and found CNV variation in three of them, however the study did not include any controls [129]. One case had a three megabase (Mb) duplication on chromosome 8, as well as a 4.4 Mb deletion on chromosome 22, and based on this, as well as a detailed family history, it is clear in retrospect that this infant had a syndromic genetic disease.…”
Section: Copy Number Variationmentioning
confidence: 91%
See 1 more Smart Citation
“…CNVs that effect critical developmental genes may cause disease. Toruner et al investigated 27 SIDS cases, and found CNV variation in three of them, however the study did not include any controls [129]. One case had a three megabase (Mb) duplication on chromosome 8, as well as a 4.4 Mb deletion on chromosome 22, and based on this, as well as a detailed family history, it is clear in retrospect that this infant had a syndromic genetic disease.…”
Section: Copy Number Variationmentioning
confidence: 91%
“…These areas on chromosome 6 include the major cluster of histone genes, and it is plausible that dosage of histone-encoding genes has an impact on their expression, and thus in turn on the global regulation of gene expression. The observed CNVs should however, according to the authors, not be regarded as a causative factor for SIDS, but rather as a predisposing genetic factor [129].…”
Section: Copy Number Variationmentioning
confidence: 98%
“…As mentioned before, in vitro studies of genetic variants of unknown significance (GVUS) should be performed in order to clarify their pathogenic role. In addition, the death could be also due to copy number variation (CNV), previously reported in SIDS cases [26]. Recently, organ specific miRNA dysregulation has been suggested to pathogenesis of SIDS [27], despite further studies should be performed to elucidate the role of miRNA in SIDS.…”
Section: -Discussionmentioning
confidence: 99%
“…Array comparative genome hybridization (aCGH) has been successful in identifying such mutations in other sporadic diseases with complex etiology including autism, schizophrenia, Crohn’s disease, and susceptibility to HIV infection (Gonzalez et al 2005; Fellermann et al 2006; Lee et al 2006; Scherer et al 2007; Sebat et al 2007; Morrow et al 2008; Walsh et al 2008). Indeed, by applying aCGH Toruner et al, (2009) identified CNVs in 3 out of 27 SIDS cases (11%), including large-scale duplications and deletions in the region of the genome where the major cluster of histone genes is located (Toruner et al 2009). The precise pathway(s) through which the CNVs identified by Toruner et al, (2009) contributed to the death of the infants is unclear and remains to be determined.…”
Section: Discussionmentioning
confidence: 99%